Pompa Air Hemat Energi dan Ramah Lingkungan menggunakan Kincir sebagai Tenaga Penggerak - Aminuddin, Jamrud; Sunardi; Mukhtar Effendi; Wihantoro; Aris Haryadi (Insan Kreasi Media, 2023)
A water pump with a wheel as the driving force has been successfully realized in Plana Village, Banyumas Regency, Central Java Province. This activity was carried out with the fish cultivator group, namely Tirta Lestari. The group uses the flow of the Serayu River as a water source for irrigating fish ponds. The position of the fish pond is about 5-6 meters higher than the river flow, so the water removal process is carried out using a water pump. Since the position of the fish pond is very far from electricity, the only solution for water supply is to use an engine-powered water pump so that the group's profits have yet to be maximized. Therefore, the water pump is a development of the research results and service carried out at the Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Jenderal Soedirman. In this activity, small-scale water pump design will be socialized as a pilot for the group to be developed on a large scale. The partner group enthusiastically welcomed the pump successfully realized because the design was simple and easy to make.